2012
DOI: 10.1007/s00404-012-2523-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose magnesium sulphate in the control of eclamptic fits: a randomized controlled trial

Abstract: The effectiveness of low-dose regimen of magnesium sulphate appeared comparable to the 'standard dose regimen'. Low-dose regimen may guarantee more safety and in an environment (such as ours) where cost is an important determinant of accessibility to qualitative health services, it is certainly attractive. More studies are needed to establish the place of low-dose regimen of magnesium sulphate in the management of eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…The findings indicated that the shortened postpartum course was as effective as the Pritchard regimen to manage eclampsia. While Chama and Geidam shortened the postpartum maintenance in their study, Abdul et al instead modified the antepartum loading and maintenance doses (Abdul, et al, 2013). During their study, Abdul et al randomized 72 patients into standard dose (n=33) and low dose (n=39) groups.…”
Section: Mgso4 Dosagementioning
confidence: 99%
“…The findings indicated that the shortened postpartum course was as effective as the Pritchard regimen to manage eclampsia. While Chama and Geidam shortened the postpartum maintenance in their study, Abdul et al instead modified the antepartum loading and maintenance doses (Abdul, et al, 2013). During their study, Abdul et al randomized 72 patients into standard dose (n=33) and low dose (n=39) groups.…”
Section: Mgso4 Dosagementioning
confidence: 99%
“…Several studies showed a recurrence rate of 4-6% with low dose magnesium sulphate therapy. [9][10][11] The recurrence rate with standard protocol reported in collaborative eclamptic trial, the largest multicentre randomized controlled trial ranged between 5.7% and 13.2%. Suman et al and Begum R, of Dhaka have concluded that the low dose magnesium sulphate therapy is as effective as standard Pritchard's regime in the Asian group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed a recurrence rate of 4-6% with low dose magnesium sulphate therapy. [10][11][12] The recurrence rate with standard protocol reported in collaborative eclamptic trial, the largest multicentre randomized controlled trial ranged between 5.7% and 13.2%. The two Asian studies one by Suman P et al and another by R. Begum of Dhaka have concluded that the low dose magnesium sulfate therapy is as effective as standard Pritchard's regime in the Asian Group.…”
Section: Discussionmentioning
confidence: 99%